Monster Cinema - Grant, Barry Keith, 1947- (Book collections on Project MUSE., 2018)
"Monster Cinema introduces readers to a vast menagerie of movie monsters. Some are gigantic, like King Kong or the kaiju in Pacific Rim, while others are microscopic. Some monsters appear uncannily human, from serial killers like Norman Bates to the pod people in Invasion of the Body Snatchers. And of course, other movie monsters like demons, ghosts, vampires, and witches emerge from long folklore traditions. Film expert Barry Keith Grant considers what each type of movie monster reveals about what it means to be human and how we regard the world. Armed with an encyclopedic knowledge of film history, Grant presents us with an eclectic array of monster movies, from Nosferatu to Get Out. As he discovers, although monster movies might claim to be about Them!, they are really about the capacity for horror that lurks within each of us"--